2023
DOI: 10.1111/phn.13254
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of people who use injection drugs with accessing hepatitis c testing and diagnosis in western countries: A scoping review

Nikki Ho,
Amanda Vandyk,
Cynthia Horvath
et al.

Abstract: BackgroundThe purpose of this scoping review was to summarize the literature that reported on the experiences of people who use injection drugs’ access to hepatitis C testing and diagnosis in Western countries.MethodsThe initial search was conducted in 2020 and an updated review was completed in 2022. Seven electronic databases were searched using a peer‐reviewed search strategy and included: full‐text, peer‐reviewed studies with people who inject(ed) drugs, hepatitis C testing or diagnosis, conducted in Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…A recent study of 200 rapid reviews from the Canadian Agency for Drugs and Technologies in Health found that peer reviews of literature search strategies significantly assisted in retrieving pertinent publications (Spry & Mierzwinski-Urban, 2018). Encouragingly, there is an emerging trend of nurse-authored publications that incorporate peerreviewed literature (e.g., Ho et al, 2024). Nurses must keep abreast of new trends and develop or enhance collaboration with librarians and other academic search professionals to produce systematic reviews of the highest quality.…”
mentioning
confidence: 99%
“…A recent study of 200 rapid reviews from the Canadian Agency for Drugs and Technologies in Health found that peer reviews of literature search strategies significantly assisted in retrieving pertinent publications (Spry & Mierzwinski-Urban, 2018). Encouragingly, there is an emerging trend of nurse-authored publications that incorporate peerreviewed literature (e.g., Ho et al, 2024). Nurses must keep abreast of new trends and develop or enhance collaboration with librarians and other academic search professionals to produce systematic reviews of the highest quality.…”
mentioning
confidence: 99%